(untitled) (Journal of Social Sciences Review, 2025)
This study aimed to measure the association among metacognition, psychological resilience and suicidal ideation in students. Cross-sectional survey design was used to draw sample. Two stage sampling technique was used in this study. Target population for the present study were student of 11 to 17 years from Gujrat and Lalamusa. Questionnaires were used to test the hypothesized relationships. The findings of the study showed that there was a strong positive and significant correlation between meta-cognition and psychological resilience (r= .616***, p-value=.000), however a non-significant correlation between meta-cognition and suicidal ideations (r=-.03, p-value=.368) was found. Findings of the study infer that the ability of metacognition is playing important role in increasing psychological resilience among students. In order to reduce the negative tendencies among students, they need to be psychologically more resilient.